2015
DOI: 10.1002/ejoc.201500585
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Aldol Reaction of α,α‐Disubstituted Acetaldehydes Catalyzed by Diphenylprolinol Silyl Ether for the Construction of Quaternary Stereogenic Centers

Abstract: The asymmetric cross-aldol reaction of α,α-disubstituted acetaldehydes with commercial ethyl glyoxylate polymer was successfully catalyzed by diphenylprolinol silyl ether 3The aldol reaction is one of the most useful carbon-carbon bond forming reactions in organic chemistry.[1] After the pioneering discovery of the intermolecular proline-mediated aldol reaction of aldehydes and ketones by List, Lerner and Barbas in 2000, there has been great progress in the field of organocatalysed asymmetric aldol chemistry.[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A diphenylprolinol trimethylsilyl ether ( Cat E‐6) catalysed aldol reaction of ethyl glyoxate 19 with α, α‐disubstituted acetaldehydes 20 was demonstrated by Hayashi et al (Scheme 8). [66] Interestingly, the inclusion of an acid additive to the reaction drastically reduced the reaction time but was also accompanied by a decrease in enantioselectivity. Gratifyingly, the introduction of Schreiner's thiourea catalyst ( Cat 6) drastically reduced the reaction time whilst improving the enantioselectivity.…”
Section: Enamine Catalysismentioning
confidence: 99%
“…A diphenylprolinol trimethylsilyl ether ( Cat E‐6) catalysed aldol reaction of ethyl glyoxate 19 with α, α‐disubstituted acetaldehydes 20 was demonstrated by Hayashi et al (Scheme 8). [66] Interestingly, the inclusion of an acid additive to the reaction drastically reduced the reaction time but was also accompanied by a decrease in enantioselectivity. Gratifyingly, the introduction of Schreiner's thiourea catalyst ( Cat 6) drastically reduced the reaction time whilst improving the enantioselectivity.…”
Section: Enamine Catalysismentioning
confidence: 99%
“…It was employed by Hayashi et al to catalyze the cross-aldol reaction of α,αdisubstituted acetaldehydes 100 with commercially available ethyl glyoxylate 4 a to construct all-carbon quaternary stereogenic center-bearing aldol adducts 103 in good enantioselectivities but with poor diastereoselectivities (Scheme 30). [93] They found that N,N-bis [3,5-bis(tri-fluoro-methyl)-phenyl]thiourea 102 is an effective additive that not only accelerates the reaction, but also increases the enantioselectivity. Using this process, a class of analogs 104 of L-PL was obtained following reduction with NaBH 4 .…”
Section: Chiral Organo-and Transition Metal Catalystsmentioning
confidence: 99%
“…To the best of our knowledge, catalytically asymmetric preparation of these 1,4-dicarbonyls is rarely reported, except for the recently disclosed reaction of ethyl glyoxylate and limited α-branched aldehydes in insufficient enantioselectivity. , Mahrwald and co-worker made a seminal contribution in performing the cross-aldol reaction of ethyl glyoxylate with enolizable aldehydes, achieving good yields and enantioselectivity (85% yield and 79% ee) with 10% l -His as an organocatalyst . Additionally, Hayashi’s group employed diphenylprolinol silyl ether to catalyze the same reaction to construct all-carbon quaternary stereogenic centers in moderate to good enantioselectivity but with poor diastereoselectivity . And notably, the reaction of α-branched aldehydes and α-ketoaldehydes for 1,4-dicarbonyls has not been disclosed to date.…”
mentioning
confidence: 99%
“…Then, the reaction was extended to explore the asymmetric α-branched aldehyde with an α-carbon stereocenter to construct 1,4-dicarbonyls bearing an acyclic all-carbon quaternary stereocenter (Scheme ). Highly enantioselective construction of an acyclic all-carbon quaternary stereocenter is a big challenge for the numerous degrees of freedom of the molecule structure. , Under the reconstructed reaction conditions (for data for reoptimization of the reaction conditions, see p S4 in Supporting Information), all reactions proceeded smoothly and uniformly achieved excellent enantioselectivity. The predominant diastereomers are anti, determined by X-ray analysis of the crystal of 6a .…”
mentioning
confidence: 99%
See 1 more Smart Citation